Prediction of quasi‐static elastic modulus for polyethylene‐terephthalate‐glycol prepared from fused deposition modeling. (17th January 2023) - Cui, Xinrui; Jar, P.‐Y. Ben
Abstract: This article is concerned about change of elastic modulus as a function of raster angle used in the fused deposition modeling and applicability of laminate theory to prediction of the elastic modulus. Polyethylene terephthalate glycol (PETG) was used for the experimental testing. In view that PETG shows viscous deformation which was not considered in the laminate theory, quasi‐static (QS) component of the elastic modulus was used to examine the applicability of laminate theory, which was achieved by extraction of the QS stress response to deformation through stress relaxation and then finite element modeling of the slope for the load–displacement curve before the relaxation. Two analytical approaches were used to examine the laminate theory. One was known as the mechanics of materials approach that considers matrix properties from the intralayer regions, and the other the elasticity model approach that also considers the interlayer regions. The study found that both approaches provided reasonable estimation of the QS elastic modulus but their values were slightly over the measured values. We provide evidence to suggest that the prediction accuracy could be improved by considering the change of interlayer filament contact with the change of raster angle. Abstract :